2022
DOI: 10.1111/apm.13213
|View full text |Cite
|
Sign up to set email alerts
|

Gene polymorphisms of TLR10: effects on bacterial meningitis outcomes in Angolan children

Abstract: This study examined whether gene polymorphisms for toll‐like receptor 10 (TLR10) associated with the susceptibility to and outcomes of bacterial meningitis (BM) in Angolan children. The study cohort consisted of 190 BM patients and the determination of ten single‐nucleotide polymorphisms (SNPs) by Sanger sequencing. Patients with BM caused by Streptococcus pneumoniae who carried the following variants of TLR10 SNPs exhibited an increased risk of coexisting pneumonia: rs10004195 (T > A) (p = 0.025), rs10856837 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…This increase in expression suggests that TLR10 may play a role in regulating B-cell function and B-cell-related diseases. In fact, human TLR10 polymorphisms have been associated with a broad range of diseases, including bacterial infections, cancer, and autoimmune diseases [30][31][32]. Zhang et al [33] found a positive correlation between rheumatoid arthritis disease activity and increased TLR10 expression in B cells.…”
Section: Introductionmentioning
confidence: 99%
“…This increase in expression suggests that TLR10 may play a role in regulating B-cell function and B-cell-related diseases. In fact, human TLR10 polymorphisms have been associated with a broad range of diseases, including bacterial infections, cancer, and autoimmune diseases [30][31][32]. Zhang et al [33] found a positive correlation between rheumatoid arthritis disease activity and increased TLR10 expression in B cells.…”
Section: Introductionmentioning
confidence: 99%